Buckling and collapse capacity of prestressed steel tube stayed columns with one and two crossarms. (November 2018) - Machacek, Josef; Pichal, Radek
Abstract: Prestressed tube stayed columns with one and two crossarms are investigated. The analyses are performed using SCIA Engineer software and ANSYS package and validated by tests of four stayed columns. First, the investigations concern the ideal (perfect) columns and cover linear buckling analyses (LBA) and geometrically nonlinear analyses (GNIA) to obtain critical loads and buckling modes under various prestressing levels. Second, the collapse loadings of the imperfect columns with initial deflections required by Eurocode EN 1993-1-1 are analysed with respect to relevant initial deflection modes and material behaviour (elastic for mild steel, nonlinear for stainless steel). All the analyses are performed for geometrical characteristics of the tested columns and the results concerning both the column with one or two crossarms are set against each other to assess the respective effectivity. In addition, the geometrical analysis of the prestressed ideal column with two crossarms and respective formulas concerning optimal prestressing and maximal critical loading are presented. Finally some recommendations for practical use are suggested. Highlights: Critical loadings of "perfect" (ideal) prestressed stayed columns and maximal loadings of "imperfect" (real) prestressed stayed columns of both columns with one and two crossarms made of stainless steel are presented. Efficiency of the prestressed stayed columns with two crossarms in comparison with systems having just one crossarm is demonstrated. Influence of sliding of stays at crossarm support is clarified.